Cultural identity and the purposes of God: a biblical theology of ethnicity, nationality, and race - Bryan, Steven M. (Crossway, 2022)
"The purpose of God in Scripture is to form one people whose devotion to God does not displace or obscure particular cultural identities but incorporates, connects, and renews them, thereby generating a rich variety of practices that constitute the total way of life of the one people of God"--